A Study on Influence of Psychological Capital of Chinese University Teachers Upon Job Thriving: Based on Motivational Work Behavior as an Intermediary Variable. (April 2021) - Liu, Xiaoxia; Lyu, Bei; Fan, Jiayu; Yu, Shu; Xiong, Ying; Chen, Hui
With the continuous development of the information process, a series of revolutionary changes are occurring in universities such as knowledge acquisition methods, teaching methods, as well as the relation between teaching and learning, which lead to new and higher requirements for teaching staff. Combining the development requirements of China's new era, starting from the perspective of capital development in universities, we should discuss the influence of universities teachers' psychological capital on job thriving. Through the literature, we found that the psychological capital of universities teachers cannot affect the job thriving directly. Therefore, we would try to find an intermediary variable-motivational work behavior and establish an intermediary model to study the relationship between variables. Through the establishment of models, the use of empirical analysis methods, analysis the data from electronic questionnaires, use software analysis, and we reveal the role of university teachers' psychological capital on the job thriving, and how to improve teachers' job thriving, the organization brings greater benefits to provide countermeasures and suggestions and provides more new enlightenment for the management of universities.